2020
DOI: 10.1111/jonm.13122
|View full text |Cite
|
Sign up to set email alerts
|

The influence of experiences of involvement in the COVID‐19 rescue task on the professional identity among Chinese nurses: A qualitative study

Abstract: In December 2019, coronavirus disease 2019 (COVID-19) was first reported in Wuhan, Hubei Province in China, and then, it expanded quickly, resulting in unprecedented remarkable threats to the public health, not only to China, but also worldwide. To efficiently stop the rapid spread of the epidemic, Chinese government adopted multiple response policies including traffic control, home isolation, modifying the regular wards into isolation wads and building new hospitals for infected people. Meanwhile, medical wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
153
1
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(177 citation statements)
references
References 25 publications
12
153
1
11
Order By: Relevance
“…As the time spent in the isolation unit doubled due to staffing shortages, the participants experienced extreme stress and fatigue. The number of patients kept rapidly increasing, and the shortage of nurses caused tremendous fatigue, comparable to the situation described in a study from China in which some staff were reported to be sleeping while standing due to extreme fatigue [19,33].…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…As the time spent in the isolation unit doubled due to staffing shortages, the participants experienced extreme stress and fatigue. The number of patients kept rapidly increasing, and the shortage of nurses caused tremendous fatigue, comparable to the situation described in a study from China in which some staff were reported to be sleeping while standing due to extreme fatigue [19,33].…”
Section: Discussionmentioning
confidence: 53%
“…Meanwhile, the nurses experienced stigma because they provided care to COVID-19 patients. COVID-19 spread rapidly to many more people than previous infectious diseases, leading to the stigmatization of COVID-19 patients and healthcare professionals who treat them [33]. The stigma described by the participants was similar to that in a study reporting that nurses caring for MERS patients were forbidden from riding in elevators, and their children's kindergarten attendance was denied [25,35].…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations